The Influence of Health Education about Anemia Using Audiovisual Media on Knowledge and Attitude Adolescent Girls in MTS Sabilarrasyad Samarinda - Hayati, Elinda Nor; Hazanah, Sri; Bernadetha, Bernadetha (PT FORMOSA CENDEKIA GLOBAL, 2024)
Adolescent girls are susceptible to anaemia due to blood loss during menstruation. The purpose of this study was to identify the influence of health education regarding anaemia, utilising audiovisual media, on the knowledge and attitudes of adolescent girls in MTS. Sabilarrasyad Samarinda. This study employed a quantitative methodology utilising a pre-experimental design, specifically a one-group pre-test and post-test framework. The number of students with increased knowledge rose from 34 (66.7%) to 51 (100%). It is known that 49 out of 50 pupils (98%) with average knowledge demonstrated improvement. For the attitude category score, 45 pupils (88.2%) exhibited an average attitude. The Wilcoxon test reveals a P-Value of 0.000 for the knowledge variable and a P-Value of 0.000 for the attitude variable. The impact of health education regarding anaemia, utilising audiovisual means, on the knowledge and attitudes of adolescent girls.